IMPLICATIONS OF MORAL EDUCATION LAWRENCE KOHLBERG AND KH AHMAD DAHLAN ON THE RELIGIOUS BEHAVIOR OF STUDENTS - Daimah Sholihah; Zainun Wafiqatun Niam (Sunan Kalijaga International Journal on Islamic Educational Research, 2020)
The reality of the Indonesian nation experienced an extraordinary moral crisis, marked by the widespread practice of KKN in the institution of the government and the many immoral behavior among the younger generation. This happens because there is no maximum implementation of moral education in schools, so moral values ​​are not realized perfectly. Therefore, there is a need to revitalize the implementation of moral education in schools. This research is a library research (library research) because the entire research process utilizes a variety of libraries that are relevant to the problem under study. The results showed that Lawrence Kohlberg's thoughts were secular, whereas Ahmad Dahlan's thoughts were religious. The concept of moral education both have similarities and differences. Both of their thoughts also have implications for the religious behavior of students, Lawrence Kohlberg shaped religious behavior through exemplary methodology, self-introduction, cognitive stimulation and empathy development as in the concept of moral education. Ahmad Dahlan shapes the religious behavior of students through teaching science and charity. Moral values ​​are taught to students to then be practiced in everyday life.